Analisis Strategi Optimalisasi Penerimaan Pajak Di Sektor Ekonomi Informal - Larosa, Wilan Rias Mei; Halawa, Atriani (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze tax revenue optimization strategies in the informal economy sector in Indonesia, which is one of the largest sectors but has not been fully exploited in national tax revenue. In this research, a qualitative approach is used with a case study method on small and medium enterprises operating in the informal sector. Data were collected through in-depth interviews, observations, and literature studies related to taxation policies and characteristics of the informal economy sector. The results show that the main obstacles to tax revenue in this sector are low tax awareness, lack of understanding of taxation, and limited infrastructure and accessibility of tax services among informal economy actors. The discussion in this study highlights the need for innovative strategies such as continuous improvement of tax education, simplification of tax administration procedures, and the application of digital technology to expand the informal sector taxpayer base. In addition, the utilization of tax incentives is considered capable of encouraging more active participation of informal sector actors in tax compliance. The conclusion of this study is that optimizing tax revenue in the informal economy sector requires a holistic approach that combines education, technology, and appropriate incentive policies. With the right strategy, the informal economy sector can become a significant contributor to increasing national tax revenue, while encouraging the integration of informal economic actors into the formal economic system. This study recommends collaboration between the government and educational institutions to create effective tax literacy programs and the development of user-friendly digital applications for informal businesses.